(3HOjYjI GdTjN CHh GdhaGs - (3CHh GdhaG eMeO Hf YeQs ((3YeQ CfSi Hf eMeO OjH GdUbYGf GdHjQhJi s)
(3ChdgG (B:s
(3HQGYJi ai EHJOG eOMi dPi Sde bO ESJgdJ HOeY aGV cGdOje s
(3BNQgG (B:s
(3HOCJ ajg hai ChUGag eOMkG CQLh HeSc NJGei MSf eNJJe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdHdGZIs